2019
DOI: 10.1182/bloodadvances.2018025874
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cardiovascular and arteriothrombotic adverse events in chronic-phase CML patients after frontline TKIs

Abstract: Cardiovascular or arteriothrombotic adverse events (CV- or AT-AEs) are reported in chronic myeloid leukemia (CML) patients treated with tyrosine kinase inhibitors (TKIs). The incidence and characteristics across different TKI have not been systematically analyzed. We analyzed 531 patients treated with frontline TKIs in different prospective trials: imatinib 400 mg (n = 71) and 800 mg (n = 203), nilotinib (n = 108), dasatinib (n = 106), and ponatinib (n = 43). Characteristics and incidence of new-onset CV-AEs a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 38 publications
7
72
1
Order By: Relevance
“…20 One study showed that the Systematic Coronary Risk Evaluation (SCORE) assessment may be a useful tool for identifying those with a higher risk of developing AOEs while on ponatinib treatment. 15 Jain et al 21 recently published a study using data from several different clinical trials with CP-CML patients who were treated with TKIs, to evaluate their cardiovascular impact, and found that ponatinib was associated with the highest incidence of CAEs/AOEs. Most of the patients in this cohort were at least in their third line of therapy upon starting ponatinib and .70% of the CP-CML patients were on nilotinib, which has been shown to increase the risks of cardiac ischemic events and peripheral arterial occlusive disease.…”
Section: Discussionmentioning
confidence: 99%
“…20 One study showed that the Systematic Coronary Risk Evaluation (SCORE) assessment may be a useful tool for identifying those with a higher risk of developing AOEs while on ponatinib treatment. 15 Jain et al 21 recently published a study using data from several different clinical trials with CP-CML patients who were treated with TKIs, to evaluate their cardiovascular impact, and found that ponatinib was associated with the highest incidence of CAEs/AOEs. Most of the patients in this cohort were at least in their third line of therapy upon starting ponatinib and .70% of the CP-CML patients were on nilotinib, which has been shown to increase the risks of cardiac ischemic events and peripheral arterial occlusive disease.…”
Section: Discussionmentioning
confidence: 99%
“…These must be considered when selecting a TKI for a patient with comorbidities [80], because some are contraindications for using a specific TKI first-line. Previous or concomitant arteriovascular disease represents a strong contraindication to nilotinib first-line and ponatinib second or third line [41,52,55,61,62,77,79,81,82], unless there is unique need. Respiratory failure and previous or concomitant pleuro-pulmonary disease are strong contraindications to dasatinib first line.…”
Section: Toxicity Side-effects and Complicationsmentioning
confidence: 99%
“…One of the most serious AEs reported with ponatinib in adult patients is arterial thrombotic events (ATEs), concern for which halted the completion of a phase 3 trial of ponatinib versus imatinib in adult patients with newly diagnosed CML (EPIC) (Lipton et al , ; Jain et al , ). The EPIC study and phase 2 trial of ponatinib in adults with Ph + ALL and CML (PACE) demonstrated that ATEs were much more common in older patients and those with pre‐existing cardiovascular risk factors (Cortes et al , ; Lipton et al , ).…”
Section: Patient and Disease Characteristics Treatment Details Toximentioning
confidence: 99%